Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00436-012-2876-z
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitocidal activity of Solanum xanthocarpum fruit extract and copepod Mesocyclops thermocyclopoides for the control of dengue vector Aedes aegypti

Abstract: The present study was carried out on Solanum xanthocarpum fruit extract and copepods Mesocyclops thermocyclopoides, which were assessed for the control of dengue vector, Aedes aegypti, under laboratory conditions. The medicinal plants were collected from the outskirts of Bharathiar University, Coimbatore, Tamil Nadu, India. The shade-dried fruit materials were extracted by employing the Soxhlet apparatus with methanol (organic solvent) 8 h and the extracts were filtered through a Buchner funnel with Whatman nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…This has been demonstrated for various species of copepods (e.g., M. edax [58], M. thermocyclopoides [54], Megacyclops formosanus [72], M. aspericornis [56]), tadpoles (e.g., Hoplobatrachus tigerinus [70]), fish (e.g., Gambusia affinis [29], Poecilia reticulata [73], Carassius auratus [74], Aplocheilus lineolatus [21]), odonate young instars (e.g., Anax immaculifrons nymphs [75], Brachydiplax sobrina nymphs [76]), and water bugs (e.g., Diplonychus indicus [77]). This opportunity should be explored further, since the exploitation of synergies between ultra-low doses of plant-fabricated mosquitocides and biological control agents may represent a further control option readily available in tropical and sub-tropical developing countries worldwide [13].…”
Section: Using Biocontrol To Kill Mosquitoesmentioning
confidence: 97%
See 1 more Smart Citation
“…This has been demonstrated for various species of copepods (e.g., M. edax [58], M. thermocyclopoides [54], Megacyclops formosanus [72], M. aspericornis [56]), tadpoles (e.g., Hoplobatrachus tigerinus [70]), fish (e.g., Gambusia affinis [29], Poecilia reticulata [73], Carassius auratus [74], Aplocheilus lineolatus [21]), odonate young instars (e.g., Anax immaculifrons nymphs [75], Brachydiplax sobrina nymphs [76]), and water bugs (e.g., Diplonychus indicus [77]). This opportunity should be explored further, since the exploitation of synergies between ultra-low doses of plant-fabricated mosquitocides and biological control agents may represent a further control option readily available in tropical and sub-tropical developing countries worldwide [13].…”
Section: Using Biocontrol To Kill Mosquitoesmentioning
confidence: 97%
“…Several species of copepods, such as Cyclops vernalis , Megacyclops formosanus , Mesocyclops (M.) aspericornis , M. edax , M. guangxiensis , M. longisetus and M. thermocyclopoides , have been reported as active predators of mosquito young instars [32,52,53,54,55,56,57,58]. Operationally, the use of copepod predators against mosquitoes in urban and semi-urban habitats is not expensive and requires minimal labour for colony maintenance, highlighting their easy and cheap potential as mass-reared biocontrol agents [59,60].…”
Section: Using Biocontrol To Kill Mosquitoesmentioning
confidence: 99%
“…Mesocyclops thermocyclopoides is a predator of the Ae. aegypti mosquito and its predatory efficiency increases by 8.7% in the presence of Solanum xanthocarpum fruit extract (Mahesh Kumar et al, 2012 ). Simple protocols have been developed for breeding Copepod species for maintenance and mass propagation prior to their release as biocontrol measures (Suarez et al, 1992 ).…”
Section: Prevention and Control Strategies Countering The Zika Virusmentioning
confidence: 99%
“…A combined bioefficacy of the fruit extracts of Solanum xanthocarpum and copepods of Mesocyclops thermocyclopoides was assessed for the control of A. aegypti , respectively [ 91 ]. The S. xanthocarpum fruit extract revealed significant larval mortality to A. aegypti 1st–4th instar larvae exposed to dosage of 100–300 ppm (the highest LC 50 = 253.18 ppm).…”
Section: Medicinal Plants Used As Agents For Vector Controlmentioning
confidence: 99%
“…The authors reported an increase in the percentage of copepod predatory efficiency in the extract treated sample (8.7%) as compared to 6.5 % in samples without the extract. This increase in predation efficiency was opined by the authors to possibly be due to the detrimental effects of the extract active principle compound (solanocarpine and solanocarpidine) on the mosquito larvae [ 91 ].…”
Section: Medicinal Plants Used As Agents For Vector Controlmentioning
confidence: 99%